An artificial graphite composite material for energy storage battery and its preparation method and application
By adopting artificial graphite composite materials with core-shell structures, combined with pre-carbonization, low-temperature graphitization and multi-layer coating technology, the problem of small increase in cycle life in the existing technology is solved, and the cycle life of energy storage batteries is significantly improved. Rate performance.
Patent Information
- Application Number
- CN202410526229.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-04-29
AI Technical Summary
The existing technology of crushing, shaping and grading controls the particle size distribution of artificial graphite, reduces the fine powder content, and improves the cycle life of energy storage batteries, but the improvement is not large, and the circulation performance of large-magnification and long-cycle is not much improved.
Artificial graphite composite material adopts core-shell structure, with the inner core of graphite, and the outer shell consists of an inorganic lithium salt composite layer and a polymer organic lithium cladding layer. It improves the structural stability of the material through pre-carbonization and low-temperature graphitization and coats inorganic lithium Salts and conductive agents improve electron and ion conductivity, and use organic lithium salts to reduce side reactions and improve circulation performance.
It significantly improves the cycle life and rate performance of energy storage batteries, improves high-temperature circulation performance and liquid retention performance, and reduces expansion and lithium ion losses.
Smart Images

Figure CN118448600B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery material preparation, and in particular to an artificial graphite composite material used in energy storage batteries, and a preparation method and application thereof. Background Art
[0002] As the market's requirements for the cycle life of energy storage batteries increase, the negative electrode is a key factor affecting its cycle life. At present, the negative electrode materials on the market are mainly artificial graphite, which can meet the cycle requirements of ≤10,000 weeks. In order to further improve the cycle life of the battery, it is necessary to surface treat the artificial graphite and improve its structure to reduce expansion and reduce the loss of lithium ions during charging and discharging to increase life, such as reducing the content of graphite fine powder, reducing the material interlayer spacing, and reducing the lithium ions consumed by SEI during charging and discharging. For example, patent application number CN202210552076.X discloses a long-life artificial graphite negative electrode material for energy storage and its preparation method and application. The patent of this invention mainly controls the particle size distribution in isotropic coke by first adopting crushing, shaping and grading technology, reduces the fine powder content, and improves the life, but the improvement is not large, and the cycle performance of large rates and long cycles is not improved much. Therefore, there is an urgent need in this field to develop an artificial graphite composite material for energy storage batteries. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide an artificial graphite composite material for energy storage batteries and a preparation method and application thereof, so as to solve the existing problem that by first adopting crushing, shaping and grading technology, the particle size distribution in isotropic coke is controlled, the fine powder content is reduced, and the life is increased, but the improvement is not large, and the cycle performance of large rate and long cycle is not improved much.
[0004] In order to achieve the above object, the present invention adopts the following technical solution:
[0005] The invention provides an artificial graphite composite material for an energy storage battery. The artificial graphite composite material for the energy storage battery is a core-shell structure, wherein the core is graphite, and the shells are, from the inside to the outside, a first shell layer of an inorganic lithium salt composite layer and a second shell layer of a high molecular polymer organic lithium coating layer; the thickness ratio of the core, the first shell layer and the second shell layer is 70-90:5-15:5-15.
[0006] The present invention also provides a method for preparing the artificial graphite composite material used in the energy storage battery, comprising the following steps:
[0007] (1) crushing, pre-carbonizing and low-temperature graphitizing coal-based pitch coke in sequence to obtain an artificial graphite precursor material;
[0008] (2) mixing a lithium salt, a dispersant, a conductive solvent, an organic solvent and an artificial graphite precursor material, and then drying and carbonizing them in sequence to obtain a lithium salt-coated graphite composite material;
[0009] (3) Polyacrylonitrile lithium, a conductive solvent, a borate coupling agent and a lithium salt-coated graphite composite material are mixed and dried to obtain an artificial graphite composite material for an energy storage battery.
[0010] Preferably, the pulverized coal-based asphalt coke has a particle size of D50=8-15 μm, and a particle size distribution of (D90-D10) / D50=1-1.2.
[0011] Preferably, the pre-carbonization temperature is 500-800° C., and the pre-carbonization time is 1-3 hours; the low-temperature graphitization temperature is 2200-2500° C., and the low-temperature graphitization time is 12-24 hours.
[0012] Preferably, the mass ratio of the lithium salt, dispersant, conductive agent, organic solvent and artificial graphite precursor material is 10-100:5-10:1-5:1000-5000:500; the lithium salt includes lithium zirconate, lithium cerate, lithium niobate, lithium titanate, lithium manganate or lithium aluminate; the dispersant includes sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate or sodium pyrophosphite; in the conductive solvent, the conductive agent independently includes carbon nanotubes, graphene or carbon black, and the solvent independently includes N-methylpyrrolidone; the mass concentration of the conductive solvent is independently 1-5%; the organic solvent includes propylene carbonate, dimethyl carbonate or diethyl carbonate.
[0013] Preferably, the drying independently comprises spray drying; the carbonization temperature is 1000-1400° C., and the carbonization time is 5-7 hours.
[0014] Preferably, in step (3), the mass ratio of polyacrylonitrile lithium, conductive solvent, borate coupling agent and lithium salt-coated graphite composite material is 10-20:1-5:0.5-2:100; the mixing temperature is 30-80°C, and the mixing time is 2-6h.
[0015] Preferably, the preparation of the lithium polyacrylonitrile comprises the following steps:
[0016] Acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate, K2S2O8 and water are mixed and reacted to obtain lithium polyacrylonitrile.
[0017] Preferably, in the preparation process of the lithium polyacrylonitrile, the mass fraction of the mixed solution consisting of acrylonitrile and water is 1-5%, the mass ratio of acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate and K2S2O8 is 10-20:10-20:5-10:1-3:0.5-2, the reaction temperature is 50-80°C, and the reaction time is 1-3h.
[0018] The present invention also provides application of the artificial graphite composite material used in the energy storage battery in preparing the energy storage battery.
[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) Pre-carbonization is used to first remove moisture and volatiles from the material to improve the structural stability of the material, and then low-temperature graphitization is used to increase the interlayer spacing of the material, reduce expansion, and increase the cycle life.
[0021] (2) Inorganic lithium salts and conductive agents are coated on the surface of artificial graphite precursor materials to enhance the electronic and ionic conductivity of the materials, improve the rate performance of the materials and utilize the good high-temperature performance of inorganic lithium salts to enhance high-temperature cycle performance. At the same time, the conductive agent is coated on the surface of graphite to reduce expansion and enhance liquid retention, thereby improving cycle performance.
[0022] (3) Organic lithium salts are coated on the surface of inorganic lithium salts, and the good compatibility of organic lithium salts with electrolytes is utilized to reduce side reactions and improve storage and cycle performance, and the good flexibility of organic lithium salts is used to reduce expansion and increase compaction density; at the same time, inorganic lithium salts are doped with borate coupling agents to improve the structural stability of the material and improve the electronic and ionic conductivity of the material, thereby improving the cycle performance.
[0023] (4) Inorganic lithium salts are coated on the surface of graphite precursors to utilize their high temperature cycle performance, high ionic and electronic conductivity, and the good compatibility of organic lithium salts with electrolytes, few side reactions, and high compaction density, and to give play to the synergistic effect between the two to improve the material's rate performance, high temperature performance, and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0025] Figure 1 This is the SEM image of the artificial graphite composite material prepared in Example 1. DETAILED DESCRIPTION
[0026] The invention provides an artificial graphite composite material for an energy storage battery. The artificial graphite composite material for the energy storage battery is a core-shell structure, wherein the core is graphite, and the shells are, from the inside to the outside, a first shell layer of an inorganic lithium salt composite layer and a second shell layer of a high molecular polymer organic lithium coating layer; the thickness ratio of the core, the first shell layer and the second shell layer is 70-90:5-15:5-15.
[0027] The present invention also provides a method for preparing the artificial graphite composite material used in the energy storage battery, comprising the following steps:
[0028] (1) crushing, pre-carbonizing and low-temperature graphitizing coal-based pitch coke in sequence to obtain an artificial graphite precursor material;
[0029] (2) mixing a lithium salt, a dispersant, a conductive solvent, an organic solvent and an artificial graphite precursor material, and then drying and carbonizing them in sequence to obtain a lithium salt-coated graphite composite material;
[0030] (3) Polyacrylonitrile lithium, a conductive solvent, a borate coupling agent and a lithium salt-coated graphite composite material are mixed and dried to obtain an artificial graphite composite material for an energy storage battery.
[0031] In the present invention, the particle size of the pulverized coal-based asphalt coke is D50=8-15 μm, and the particle size distribution is (D90-D10) / D50=1-1.2.
[0032] In the present invention, the pre-carbonization temperature is preferably 500-800°C, more preferably 550-750°C, and more preferably 600-700°C; the pre-carbonization time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; the low-temperature graphitization temperature is preferably 2200-2500°C, more preferably 2250-2450°C, and more preferably 2300-2400°C; the low-temperature graphitization time is preferably 12-24h, more preferably 14-20h, and more preferably 16-18h.
[0033] In the present invention, the mass ratio of the lithium salt, dispersant, conductive agent, organic solvent and artificial graphite precursor material is preferably 10-100:5-10:1-5:1000-5000:500, more preferably 30-80:6-9:2-4:2000-4000:500, more preferably 40-70:7-8:3:3000-3500:500; the lithium salt includes lithium zirconate, lithium cerate, lithium niobate, lithium titanate, lithium manganate or lithium metaaluminate; the dispersant includes sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate or sodium pyrophosphite; in the conductive solvent, the conductive agent independently includes carbon nanotubes, graphene or carbon black, and the solvent independently includes N-methylpyrrolidone; the mass concentration of the conductive solvent is independently preferably 1-5%, more preferably 2-4%, and more preferably 3%; the organic solvent includes propylene carbonate, dimethyl carbonate or diethyl carbonate.
[0034] In the present invention, the drying independently includes spray drying; the carbonization temperature is preferably 1000-1400°C, more preferably 1100-1300°C, more preferably 1200-1250°C; the carbonization time is preferably 5-7h, more preferably 5.5-6.5h, more preferably 6h.
[0035] In step (3) of the present invention, the mass ratio of lithium polyacrylonitrile, conductive solvent, borate coupling agent and lithium salt-coated graphite composite material is preferably 10-20:1-5:0.5-2:100, more preferably 11-18:2-4:1-1.5:100, more preferably 12-15:3:1.2:100; the mixing temperature is preferably 30-80°C, more preferably 40-70°C, more preferably 50-60°C; the mixing time is preferably 2-6h, more preferably 3-5h, more preferably 4-4.5h.
[0036] In the present invention, the preparation of lithium polyacrylonitrile comprises the following steps:
[0037] Acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate, K2S2O8 and water are mixed and reacted to obtain lithium polyacrylonitrile.
[0038] In the present invention, in the preparation process of the polyacrylonitrile lithium, the mass fraction of the mixed solution composed of acrylonitrile and water is preferably 1-5%, more preferably 2-4%, and more preferably 3%; the mass ratio of acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate and K2S2O8 is preferably 10-20:10-20:5-10:1-3:0.5-2, more preferably 12-19:12-19:6-9:2:1-1.5, more preferably 15-18:15-18:7-8:2:1.2; the reaction temperature is preferably 50-80°C, more preferably 60-70°C, and more preferably 65°C; the reaction time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h.
[0039] The present invention also provides application of the artificial graphite composite material used in the energy storage battery in preparing the energy storage battery.
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] Example 1
[0042] Preparation of polyacrylonitrile lithium mixture:
[0043] 15g of acrylonitrile was dissolved in 75g of deionized water to prepare a 2wt% solution, then 2g of methyl methacrylate and 8g of acrylic acid were added and ultrasonically dispersed at 60°C, then 1g of K2S2O8 was added dropwise to disperse evenly, then 15g of lithium hydroxide was added dropwise, and the mixture was reacted at this temperature for 2h to obtain a polyacrylonitrile lithium mixture.
[0044] The preparation of an artificial graphite composite material for an energy storage battery comprises the following steps:
[0045] (1) The coal-based pitch coke is crushed to a particle size of D50 = 10 μm, and the particle size distribution = (D90-D10) / D50 = 1.1, and then loaded into a graphitization furnace and heated to 650° C. for pre-carbonization for 2 h in a nitrogen atmosphere, and then heated to 2300° C. for low-temperature graphitization for 18 h, and then cooled to room temperature in a nitrogen atmosphere to obtain an artificial graphite precursor material;
[0046] (2) adding 8 g of sodium tripolyphosphate to 3000 g of propylene carbonate and dispersing the mixture uniformly, then adding 100 g of a 3 wt% carbon nanotube N-methylpyrrolidone solution, dispersing 50 g of lithium zirconate uniformly, then adding 500 g of a precursor material and dispersing the mixture uniformly by ultrasonication, spray drying, and carbonizing the mixture at 1200 ° C for 6 h to obtain a lithium salt-coated graphite composite material;
[0047] (3) 15 g of polyacrylonitrile lithium was added to 100 g of a 3 wt% carbon nanotube N-methylpyrrolidone conductive agent solution and dispersed evenly, and 1 g of a borate coupling agent was added and ultrasonically dispersed to obtain a coating solution, and then 100 g of a lithium salt-coated graphite composite material was added and ultrasonically dispersed at a temperature of 50°C for 4 hours, and spray-dried to obtain an artificial graphite composite material.
[0048] Example 2
[0049] Preparation of polyacrylonitrile lithium mixture:
[0050] 10g of acrylonitrile was dissolved in 1000g of deionized water to prepare a 1wt% solution, then 1g of methyl methacrylate and 5g of acrylic acid were added and heated at 50°C for ultrasonic dispersion, then 0.5g of K2S2O8 was added dropwise for dispersion, then 10g of lithium hydroxide was added dropwise and the mixture was reacted at this temperature for 3h to obtain a polyacrylonitrile lithium mixture.
[0051] The preparation of an artificial graphite composite material for an energy storage battery comprises the following steps:
[0052] (1) The coal-based pitch coke is crushed to a particle size of D50 = 8 μm, and the particle size distribution = (D90-D10) / D50 = 1.2, and then loaded into a graphitization furnace and heated to 500° C. for pre-carbonization for 3 h under a nitrogen atmosphere, and then heated to 2200° C. for low-temperature graphitization for 24 h to obtain an artificial graphite precursor material;
[0053] (2) 5 g of sodium hexametaphosphate was added to 1000 g of dimethyl carbonate and dispersed evenly, then 100 g of N-methylpyrrolidone conductive agent solution containing 1 wt% graphene was added, 10 g of lithium ceria was dispersed evenly, then 500 g of precursor material was added and ultrasonically dispersed evenly, spray dried, and carbonized at 1000 ° C for 6 h to obtain a lithium salt-coated graphite composite material;
[0054] (3) 10 g of polyacrylonitrile lithium was added to 100 g of 1 wt% graphene N-methylpyrrolidone conductive agent solution and dispersed evenly, and 0.5 g of borate coupling agent was added and ultrasonically dispersed to obtain a coating liquid, and then 100 g of lithium salt-coated graphite composite material was added and ultrasonically dispersed at a temperature of 30°C for 6 hours, and spray-dried to obtain an artificial graphite composite material.
[0055] Example 3
[0056] Preparation of polyacrylonitrile lithium mixture:
[0057] 20g of acrylonitrile was dissolved in 400g of deionized water to prepare a 5wt% solution, then 3g of methyl methacrylate and 10g of acrylic acid were added and heated at 80°C for ultrasonic dispersion, then 20g of K2S2O8 was added dropwise for dispersion, then 20g of lithium hydroxide was added dropwise and reacted at this temperature for 1h to obtain a polyacrylonitrile lithium mixture.
[0058] The preparation of an artificial graphite composite material for an energy storage battery comprises the following steps:
[0059] (1) The coal-based pitch coke is crushed to a particle size of D50 = 15 μm, and the particle size distribution = (D90-D10) / D50 = 1.0, and then loaded into a graphitization furnace and heated to 800° C. for pre-carbonization for 1 h under a nitrogen atmosphere, and then heated to 2500° C. for low-temperature graphitization for 12 h to obtain an artificial graphite precursor material;
[0060] (2) adding 10 g of sodium pyrophosphate to 5000 g of diethyl carbonate and dispersing the mixture uniformly, then adding 100 g of a 5 wt% carbon black N-methylpyrrolidone conductive agent solution, dispersing 100 g of lithium niobate uniformly, then adding 500 g of a precursor material and dispersing the mixture uniformly by ultrasonication, spray drying, and carbonizing the mixture at 1400° C. for 6 h to obtain a lithium salt-coated graphite composite material;
[0061] (3) Add 20 g of polyacrylonitrile lithium to 100 g of a 5 wt% carbon black N-methylpyrrolidone conductive agent solution and disperse evenly, and add 2 g of a borate coupling agent and ultrasonically disperse evenly to obtain a coating liquid, then add 100 g of a lithium salt-coated graphite composite material, and ultrasonically disperse at 80°C for 2 h, spray dry, and obtain an artificial graphite composite material.
[0062] Comparative Example 1
[0063] The difference from Example 1 is that no organic lithium coating is performed, that is, the lithium salt-coated graphite composite material obtained in step (2) is used as the negative electrode.
[0064] Comparative Example 2
[0065] The difference from Example 1 is that inorganic lithium coating is not performed, that is, the lithium salt-coated graphite composite material in step (3) is replaced by an artificial graphite precursor material, and the rest is the same as Example 1.
[0066] The performance of the artificial graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the test methods and results are as follows.
[0067] (1) SEM test:
[0068] The artificial graphite composite material prepared in Example 1 was subjected to SEM test, and the test results are as follows: Figure 1As shown in the figure, it can be seen that the artificial graphite composite material is a spherical particle structure with a particle size between 10 and 15 μm.
[0069] (2) Powder conductivity test:
[0070] The artificial graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for powder conductivity. The test method for powder conductivity was as follows: the powder was pressed into a block structure on a powder compaction density meter at a pressure of 2 T, and then the powder conductivity was tested using a four-probe tester. The test results are shown in Table 1.
[0071] (3) Interlayer spacing, specific surface area, particle size, OI value, and graphitization degree test:
[0072] According to GB / T 24533-2019 "Graphite Anode Materials for Lithium Ion Batteries", the interlayer spacing D002, specific surface area, particle size, and degree of graphitization of the artificial graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the OI value of the powder material was tested by XRD. The test results are shown in Table 1.
[0073] Table 1 Physical and chemical properties test results
[0074]
[0075] It can be seen from Table 1 that compared with Example 1, Comparative Example 1 is not coated with organic lithium, and has a larger specific surface area and a larger interlayer spacing; compared with Example 1, Comparative Example 2 is not coated with inorganic lithium, and has a larger specific surface area and a larger powder OI value.
[0076] (4) Button battery test:
[0077] The artificial graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are respectively assembled into button batteries. The assembly method is: add a binder, a conductive agent and a solvent to the negative electrode material, stir and slurry, apply it on a copper foil, and dry and roll to obtain a negative electrode sheet. The binder used is LA132 binder, the conductive agent is SP, the negative electrode material is the artificial graphite composite material obtained in Examples 1 to 3 and Comparative Examples 1 to 2, and the solvent is double distilled water. The proportion of each component is: negative electrode material: SP: LA132: double distilled water = 95g: 1g: 4g: 220mL; the electrolyte is LiPF6 / EC+DEC (the concentration of LiPF6 is 1.2mol / L, and the volume ratio of EC and DEC is 1:1), the metal lithium sheet is the counter electrode, and the diaphragm is polyethylene (PE), polypropylene (PP) or polyethylene propylene (PEP) composite film. The button cell was assembled in an argon-filled glove box, and the electrochemical performance test was performed on a Wuhan Blue Power CT2001A battery tester. The charge and discharge voltage range was 0.005 to 2.0 V, the charge and discharge rate was 0.1C, and its rate performance (1C / 0.1C) was tested. The test results are shown in Table 2.
[0078] Table 2 Button battery performance test results
[0079]
[0080]
[0081] It can be seen from Table 2 that the first discharge capacity and the first charge and discharge efficiency of the lithium ion battery using the artificial graphite composite material obtained in Examples 1 to 3 are significantly higher than those in Comparative Examples 1 to 2. The reason is that the graphite surface is coated with organic lithium and inorganic lithium, which reduces material defects, increases the transmission rate of lithium ions, and improves the first efficiency and rate performance.
[0082] (5) Soft pack battery test:
[0083] The artificial graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used as negative electrode materials to prepare negative electrode plates. Lithium iron phosphate was used as the positive electrode, LiPF6 solution (solvent was EC+DEC, volume ratio 1:1, LiPF6 concentration 1.3 mol / L) was used as the electrolyte, and celegard 2400 was used as the separator to prepare 5Ah soft-pack batteries. The cycle performance of the soft-pack batteries was then tested.
[0084] Cycle performance test conditions: charge and discharge current 1C / 1C, voltage range 2.8~4.2V, cycle number 500 times. Test results are shown in Table 3.
[0085] Table 3 Soft pack battery performance test results
[0086]
[0087]
[0088] It can be seen from Table 3 that the artificial graphite composite materials obtained in Examples 1 to 3 have better cycle performance as negative electrodes for soft-pack batteries than those in Comparative Examples 1 to 2. The reason is that in terms of 1C / 1C rate cycle performance, sufficient lithium ions are provided by the lithium compounds on the surface of graphite to improve the cycle performance. At the same time, the material has a low specific surface area, which reduces its side reactions, and has a narrow particle size distribution and less fine powder, which reduces its side reactions and improves the cycle performance.
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An artificial graphite composite material for energy storage battery, characterized in that: The artificial graphite composite material used in the energy storage battery is a core-shell structure, wherein the core is graphite, and the shells are, from the inside to the outside, a first shell layer of an inorganic lithium salt composite layer and a second shell layer of a high molecular polymer organic lithium coating layer; the thickness ratio of the core, the first shell layer and the second shell layer is 70-90:5-15:5-15; The method for preparing the artificial graphite composite material used in the energy storage battery comprises the following steps: (1) crushing, pre-carbonizing and low-temperature graphitizing coal-based pitch coke in sequence to obtain an artificial graphite precursor material; (2) mixing a lithium salt, a dispersant, a conductive solvent, an organic solvent and an artificial graphite precursor material, and then drying and carbonizing them in sequence to obtain a lithium salt-coated graphite composite material; (3) mixing polyacrylonitrile lithium, a conductive solvent, a borate coupling agent and a lithium salt-coated graphite composite material and drying the mixture to obtain an artificial graphite composite material for an energy storage battery; The lithium salt includes lithium cerate, lithium niobate, lithium manganate or lithium aluminate; the dispersant includes sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate or sodium pyrophosphite.
2. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: The particle size of the pulverized coal-based asphalt coke is D50=8-15 μm, and the particle size distribution is (D90-D10) / D50=1-1.
2.
3. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: The pre-carbonization temperature is 500-800° C., and the pre-carbonization time is 1-3 hours; the low-temperature graphitization temperature is 2200-2500° C., and the low-temperature graphitization time is 12-24 hours.
4. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: The mass ratio of the lithium salt, dispersant, conductive agent, organic solvent and artificial graphite precursor material is 10-100:5-10:1-5:1000-5000:500; in the conductive solvent, the conductive agent independently includes carbon nanotubes, graphene or carbon black, and the solvent independently includes N-methylpyrrolidone; the mass concentration of the conductive solvent is independently 1-5%; the organic solvent includes propylene carbonate, dimethyl carbonate or diethyl carbonate.
5. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: The drying independently includes spray drying; the carbonization temperature is 1000-1400° C., and the carbonization time is 5-7 hours.
6. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: In the step (3), the mass ratio of polyacrylonitrile lithium, conductive solvent, borate coupling agent and lithium salt-coated graphite composite material is 10-20:1-5:0.5-2:100; the mixing temperature is 30-80° C., and the mixing time is 2-6 hours.
7. The artificial graphite composite material for energy storage battery according to claim 1, characterized in that: The preparation of the lithium polyacrylonitrile comprises the following steps: Acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate, K2S2O8 and water are mixed and reacted to obtain lithium polyacrylonitrile.
8. The artificial graphite composite material for energy storage battery according to claim 7, characterized in that: In the preparation process of the lithium polyacrylonitrile, the mass fraction of the mixed solution composed of acrylonitrile and water is 1-5%, the mass ratio of acrylonitrile, lithium hydroxide, acrylic acid, methyl methacrylate and K2S2O8 is 10-20:10-20:5-10:1-3:0.5-2, the reaction temperature is 50-80°C, and the reaction time is 1-3h.
9. Use of the artificial graphite composite material for energy storage batteries according to claim 1 in the preparation of energy storage batteries.
Citation Information
Patent Citations
A long-life artificial graphite negative electrode material for energy storage and its preparation method and application
CN114933301B
Lithium ion battery cathode material and preparation method thereof and lithium ion battery
CN106299314A
Nitrogen-doped graphene-silicon composite negative pole material, preparation method thereof, and lithium ion battery
CN106876689A
Graphite composite electrode material and preparation method thereof
CN113675389A